Synthesis and Spectroscopic Analysis of S-Triazine-Linked Pyrazolone Derivatives - Yash Parmar; Dr. K. S. Nimavat; Dr. Kartik B. Vyas (International Journal of Scientific Research in Chemistry, 2025)
Pyrazolone is 5-membered heterocycle containing two adjacent nitrogen atoms. It can be viewed as a derivative of pyrazole possessing an additional carbonyl (C=O) group. Compounds containing this functional group are useful commercially in analgesics and dyes. Its play’s important role in drug discovery. Pyrazoles and pyrazolines present a wide range of biological activities. In the present study describe synthesis of various pyrazolones by reaction of N-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) acetamide with cyanuric chloride followed by reflux under ethanol using various aromatic aldehyde in the presence of alkali. All the synthesized compounds were characterized by 1HNMR, 13CNMR, IR, MASS spectroscopic techniques.